Intestinal Helminth infections and associated risk factors in dogs of Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2022)
This study was conducted to determine the prevalence and related risk factors for intestinal helminth infections in companion and stray dogs from Dhaka, Bangladesh. In total 310 fecal samples were collected from companion dogs (206 samples) and stray dogs (104 samples) from Dhaka south city corporation (DSCC) and Dhaka North city corporation (DNCC) areas. Salt flotation and formol ether concentration techniques were used to process the fecal samples. The prevalence of intestinal helminth infections in stray and companion dogs in DSCC was 48.98% and 18.02%, respectively, while in DNCC, it was 7.27% and 15.79%. Ancylostomatids showed the maximum prevalence (18.37%) followed by Toxocara canis (14.28%). Intestinal parasitic infections were more prevalent among female companion dogs (17.24%) than males (16.89%). Dogs of pure or mixed breed were prone to parasitic infections (29.09%). Outdoor access (P=0.000) and irregular deworming (P=0.000) were potential risk factors for intestinal helminth infections in companion dogs. Helminth infections in dogs could be a major public health concern. Proper sanitation measures especially in DSCC areas are necessary to check this alarming issue.Bangladesh J. Zool. 49 (3): 411-421, 2021